Treatment of a periodontally compromised patient with mini-implant anchorage. - Eduardo Yugo Suzuki (2018)
Advanced periodontal disease and its sequelae are characterized by severe attachment loss, tooth mobility, and migration. This pathology often leads to compromised function and esthetics. A multidisciplinary approach combining orthodontic, periodontic, and restorative treatment is necessary to provide complete rehabilitation both in terms of function and esthetics with a satisfactory long-term prognosis. A simple and effective treatment of an adult patient with periodontally migrated teeth using mini-implants in the maxilla and mandible is described. Mini-implant placement was aided by a 3D surgical guide, which made the procedure exceedingly safe. Gradual intrusion of the maxillary and mandibular anterior teeth was achieved with a relatively simple orthodontic force system. A significant profile improvement was observed during the 18 months of treatment due to the retraction and intrusion of the incisors in both arches. This intrusion was accomplished without any sign of apical root resorption. The mandibular incisors were uprighted 6.5 degrees, and their maxillary counterparts were uprighted 13.4 degrees. The 2-year follow-up examination revealed a stable result with an increase in periodontal attachment as well as esthetics and function. A combined orthodontic, periodontic, and restorative treatment approach with adequate patient motivation can lead to improved masticatory function, esthetics, and periodontal conditions. © 2009 BY QUINTESSENCE PUBLISHING CO, INC.